Teaching music in the secondary school: challenges and perspectives from music teachers / Rohayu Ibrahim - Ibrahim, Rohayu (2008)
This research is investigates the challenges and perspectives of music teachers at the secondary schools. Eight music teachers were selected from various secondary schools in Selangor. Pahang, Kedah and Negeri Sembilan. Data was collected through interviews. Findings of the data are presented by categorizing into the specific themes based on the research questions. Results indicate that music teachers faced a common problem of lack of music instruments, proper facilities for music classes, timetable and varying attitude towards music among other teachers and parents. Music teachers managed to work around this problem by using alternative teaching methods such as through the use of audio visual materials. Generally, all music teachers in the study repeated that their students were interested to learn music.